Agent Banking: Impact on The Financial Performance of Commercial Banks in Bangladesh - Robin, Iftekhar Ahmed; Hassan, M. Kabir (OECONOMICUS Journal of Economics, 2024)
The paper examines the effects of agent banking activities on the financial performance of commercial banks in Bangladesh. Employing bank level quarterly data for the period 2018Q1- 2021Q4, the study estimates a pooled OLS regression model to investigate the effects of agent bank specific factors on the financial performance of the related commercial banks (principal/mother bank) in terms of profitability measures, return on assets (ROA) and return on equity (ROE). The estimated regression results show that amount of loan disbursement by agent banks and number of agent banking account holders have positive and statistically significant impact on the banks’ profit. However, the number of agents and/or outlets do not necessarily affect the profitability of the principal/mother bank. The findings of this study would help the policy makers, bank management and other stakeholders for decision making and improving the performance of agent banking in developing countries like Bangladesh.